2020
DOI: 10.1186/s12985-020-1297-3
|View full text |Cite
|
Sign up to set email alerts
|

Successfully transfected primary peripherally mobilized human CD34+ hematopoietic stem and progenitor cells (HSPCs) demonstrate increased susceptibility to retroviral infection

Abstract: Transfection, the process of introducing purified nucleic acids into cells, and viral transduction, viral-mediated nucleic acid transfer, are two commonly utilized techniques for gene delivery in the research setting. Transfection allows purified nucleic acid to be introduced into target cells through chemical-based techniques, nonchemical methods or particle-based methods, while viral transduction employs genomes or vectors based on adenoviruses, retroviruses (e.g. lentiviruses), adeno-associated viruses, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…100 Of note, a recent study showed that prior transfection of CD34þ cells with plasmid DNA increases the efficiency of the following transduction procedures by threefold. 101 Stable regulation of gene expression has been reported in different studies using CRISPR/Cas9 tools 102 and Transcription Activator-Like Effector Nucleases (TALEN), 103 which are robust gene-editing systems to modify miRNA levels. In a recent study, over 80% of hPSCs were shown to undergo targeted genome editing using CRISPR-Cas9 reagents and nucleofection.…”
Section: Modulation Of Mirna Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…100 Of note, a recent study showed that prior transfection of CD34þ cells with plasmid DNA increases the efficiency of the following transduction procedures by threefold. 101 Stable regulation of gene expression has been reported in different studies using CRISPR/Cas9 tools 102 and Transcription Activator-Like Effector Nucleases (TALEN), 103 which are robust gene-editing systems to modify miRNA levels. In a recent study, over 80% of hPSCs were shown to undergo targeted genome editing using CRISPR-Cas9 reagents and nucleofection.…”
Section: Modulation Of Mirna Contentmentioning
confidence: 99%
“… 100 Of note, a recent study showed that prior transfection of CD34+ cells with plasmid DNA increases the efficiency of the following transduction procedures by threefold. 101 …”
Section: In Vitro Study Of Platelet Functionmentioning
confidence: 99%